A Review of the Antimicrobial Potential of Musca domestica as a Natural Approach with Promising Prospects to Countermeasure Antibiotic Resistance. (30th December 2022) - Niode, Nurdjannah Jane; Mahono, Charles Kurnia; Lolong, Felicia Maria; Matheos, Merina Pingkan; Kepel, Billy Johnson; Tallei, Trina Ekawati
Abstract : Drug-resistant pathogens have become a serious public health concern worldwide considering the rapid emergence and distribution of new strains, which outpace the development of antimicrobial drugs. It is a complex and serious clinical problem that can cause an epidemic of a disease; consequently, numerous research studies are conducted to determine the solution to these problems, including the development of new antibiotics derived from natural sources such as insects. The housefly ( Musca domestica L. ), an insect known as a cosmopolitan pest, possesses several qualities that can ameliorate diseases; consequently, they can be used as a bioactive component in the development of medicines. These qualities include its potential as a source of antibacterial agents. The external surface components, wings, internal organs, and whole body extract of M. domestica can all contribute antimicrobial potential due to bioactive compounds they produce. This article discusses several antimicrobial properties of M. domestica that could be utilized for healthcare benefits.